M5 The multiple sclerosis drug, glatiramer acetate, acts as a resistance breaker with antibiotics from different classes against cystic fibrosis strains of pseudomonas aeruginosa. (12th November 2019) - Murphy, RA; Harrison, J; Schelenz, S; Davies, JC
Abstract : Objectives: Glatiramer acetate (GA), licensed for the treatment of multiple sclerosis, has modest antimicrobial activity against Pseudomonas aeruginosa (Pa) 1 . Due to its chemical similarities to antimicrobial peptides, we investigated GA as an antibiotic resistance breaker of Pa when used in combination with the common antimicrobials: tobramycin (TOB), ceftazidime (CAZ), ciprofloxacin (CIP) and colistin (CST). Methods: Strains PAO1 and PA14 were inoculated into Mueller-Hinton broth at starting optical density (OD600 ) of 0.05 (∼5 × 10 6 CFU/mL). Antibiotic (TOB, CAZ, CIP or CST) was added at antibiotic-specific concentrations, ± 50 µg/mL GA. Cultures were incubated shaking (200rpm) in a 96-well plate for 16 hrs at 37°C and growth measured by hourly OD600 . Serial dilution colony counts were performed on 16 hr cultures. Results: Growth curves indicated GA improved the efficacy of TOB and CAZ against PAO1 and PA14, effects confirmed by colony counting. Maximal effect was seen at different antibiotic concentrations (table 1). GA improved the efficacy of CIP against PA01 but not PA14; GA did not enhance killing of either strain by CST. Conclusion: The repurposed drug, GA, increased efficacy of TOB & CAZ with an up to ∼80-fold decrease in Pa number. Little effect was seen with CIP and was absent with CST, possibly due to similar modes of action on the bacterial cell membrane. Co-administration of GA could allow lower doses/shorter courses of antibiotic to be just as/more effective against Pa in CF, limiting side effects, or could enhance efficacy. Differences between CF clinical Pa strains were previously observed for TOB and are being explored further as this approach may best be applied in a personalised fashion.